Student Enrollment System Model - A Proposal - Gee, Kheng Chuan (2003)
Management of student data including their personal particulars is an important area in any school administration. Usually, the personal particulars are collected during enrollment process. Apart from the manual system, there exists no specific model to guide the enrollment. The traditional manual student registration system place a heavy burden towards school administrators especially the class teachers. The management of student records already input stresses top level school managers. This project identifies and proposes a model in enrolling students to Malaysian government secondary school that allows the sharing of responsibilities among top school management, administrators, and students. The key to this redistribution of burdens and responsibilities is the web-based technologies.